Meniscus‐Guided Micro‐Printing of Prussian Blue for Smart Electrochromic Display. Issue 3 (28th November 2022) - Kim, Je Hyeong; Park, Seobin; Ahn, Jinhyuck; Pyo, Jaeyeon; Kim, Hayeol; Kim, Namhun; Jung, Im Doo; Seol, Seung Kwon
Abstract: Using energy‐saving electrochromic (EC) displays in smart devices for augmented reality makes cost‐effective, easily producible, and efficiently operable devices for specific applications possible. Prussian blue (PB) is a metal‐organic coordinated compound with unique EC properties that limit EC display applications due to the difficulty in PB micro‐patterning. This work presents a novel micro‐printing strategy for PB patterns using localized crystallization of FeFe(CN)6 on a substrate confined by the acidic‐ferric‐ferricyanide ink meniscus, followed by thermal reduction at 120 °C, thereby forming PB. Uniform PB patterns can be obtained by manipulating printing parameters, such as the concentration of FeCl3 ·K3 Fe(CN)6, printing speed, and pipette inner diameter. Using a 0.1 M KCl (pH 4) electrolyte, the printed PB pattern is consistently and reversibly converted to Prussian white (CV potential range: −0.2–0.5 V) with 200 CV cycles. The PB‐based EC display with a navigation function integrated into a smart contact lens is able to display directions to a destination to a user by receiving GPS coordinates in real time. This facile method for forming PB micro‐patterns could be used for advanced EC displays and various functional devices. Abstract : Meniscus‐guided micro‐printing of Prussian blue (PB) is realized by local crystallization of FeFe(CN)6 on a substrate confined with an ink meniscus followed by thermal reduction of Fe 3+ ions. The printed PB pattern is reversibly converted to Prussian white by conducting cyclic voltammetry in KCl electrolyte. PB‐based electrochromic displays with a navigation function in a smart contact lens are demonstrated.